High-conductivity solid-state lithium metal electrolyte membrane and preparation method thereof

By introducing inorganic fillers and ionic conductive additives into the polymer matrix, the ratio and preparation process are optimized, the problems of low conductivity and high interface impedance of solid lithium metal electrolytes are solved, high ionic conductivity and good interface stability are achieved, and the comprehensive performance and safety performance of lithium metal batteries are improved.

CN119542518APending Publication Date: 2025-02-28ZHEJIANG LINGYI NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411777008.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing solid-state lithium metal electrolyte has low conductivity, high interface impedance, and unsatisfactory lithium dendrites, which limits the practical application of lithium metal batteries.

Method used

Inorganic fillers and ionic conductive additives are introduced into the polymer matrix to optimize the proportion of each component, and a scientific and reasonable preparation process is adopted to make a thin film by solvent volatilization or hot pressing method, and heat treatment is carried out to improve the ionic conductivity and interface stability of the electrolyte.

Benefits of technology

It significantly improves the ionic conductivity and interface stability of solid lithium metal electrolytes, inhibits the growth of lithium dendrites, and improves the comprehensive performance and safety performance of lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005171730310000091
    Figure BDA0005171730310000091
Patent Text Reader

Abstract

The invention discloses a high-conductivity solid-state lithium metal electrolyte membrane and a preparation method thereof, and relates to the field of solid-state lithium metal electrolyte. According to the electrolyte, the inorganic filler and the ionic conductive additive are added into the lithium salt and the polymer matrix, so that the ionic conductivity and the stability of the electrolyte are remarkably improved. The electrolyte shows excellent thermal stability, ionic conductivity and interface stability, and is suitable for a solid-state lithium metal battery. The preparation method comprises the steps of uniformly mixing and forming the lithium salt, the polymer matrix, the inorganic filler and the ionic conductive additive. The invention provides a solution that the existing solid electrolyte is low in conductivity and poor in interface stability, and can be suitable for large-scale industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solid lithium metal electrolytes, in particular to a high-conductivity solid lithium metal electrolyte membrane and a preparation method thereof. Background Art

[0002] With the rapid development of electric vehicles, smart grids and renewable energy storage systems, high energy density and long life lithium battery technology has become a key research area in global scientific research and industry. Among them, lithium metal batteries have become an ideal candidate for the next generation of battery technology due to their extremely high theoretical specific energy density. However, traditional liquid electrolytes have safety hazards such as poor electrochemical stability, flammability, explosion, and leakage. In addition, liquid electrolytes form an unstable solid electrolyte interface layer (SEI) on the surface of the lithium metal negative electrode, which can easily lead to the growth of lithium dendrites and further cause short circuit problems, which seriously limits the practical application of lithium metal batteries.

[0003] In order to solve these problems, solid electrolytes have gradually attracted widespread attention. Solid electrolytes can not only improve the safety of lithium metal batteries, but also inhibit the growth of lithium dendrites, and improve the energy density and cycle life of batteries. However, solid electrolytes still face some major challenges in practical applications. Existing solid lithium metal electrolytes are mainly divided into three categories: polymer solid electrolytes, inorganic solid electrolytes and composite solid electrolytes.

[0004] Polymer-based solid electrolytes have good mechanical flexibility and formability and are often used in thin-film electrolyte materials. However, the ionic conductivity of pure polymer electrolytes is relatively low and usually cannot reach the conductivity level required for lithium metal batteries at room temperature. In addition, polymer electrolytes have poor chemical stability at the lithium metal anode interface and are prone to side reactions with lithium metal to form an unstable interface layer, resulting in increased interface impedance and decreased battery performance.

[0005] Inorganic solid electrolytes have high ionic conductivity and good thermal stability, and perform well under high temperature and high voltage conditions. However, inorganic electrolytes are brittle and have low mechanical strength, making it difficult to effectively inhibit the growth of lithium dendrites. In addition, the inorganic electrolyte has poor contact with the lithium metal negative electrode interface, which easily forms a high interfacial impedance and affects the battery's cycle performance.

[0006] In recent years, composite solid electrolytes have gradually become a research hotspot. By introducing inorganic fillers (such as alumina, silica, etc.) into the polymer matrix, composite electrolytes can combine the advantages of both to a certain extent, improving both ionic conductivity and enhancing mechanical strength and interface stability. Inorganic fillers can effectively improve the overall conductivity of the electrolyte, while reducing interfacial impedance and inhibiting the growth of lithium dendrites. However, the performance of composite electrolytes is still limited by material ratios, preparation processes and additive selection. Optimizing the ratio of inorganic fillers to polymer matrices and the types of additives is the key to improving the comprehensive performance of solid electrolytes.

[0007] In addition, the preparation process of solid lithium metal electrolytes also has an important influence on their final performance. The main preparation methods currently include solvent evaporation, hot pressing and solution casting. The parameters of these processes (such as temperature, pressure, molding time, etc.) have a significant impact on the microstructure and ionic conductivity of the electrolyte. Summary of the invention

[0008] In view of the problems of low conductivity, high interface impedance, and unsatisfactory lithium dendrite suppression of solid electrolytes in the prior art, the development of a solid electrolyte with both high ionic conductivity and good interface stability is the key to improving the comprehensive performance of lithium metal batteries. The present invention significantly improves the ionic conductivity and interface stability of solid lithium metal electrolytes by introducing inorganic fillers and ion conductive additives into the polymer matrix, optimizing the ratio of each component, and adopting a scientific and reasonable preparation process, providing technical support for the practical application of lithium metal batteries.

[0009] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] A highly conductive solid lithium metal electrolyte membrane and a preparation method thereof, characterized in that the steps include:

[0011] (1) Material mixing: 5-20 parts of lithium salt, 40-70 parts of polymer matrix, 5-30 parts of inorganic filler, 2-8 parts of ion conductive additive and 0.1-2 parts of conductive additive are uniformly mixed by mass, and then the mixture is dissolved in 450-900 parts of organic solvent;

[0012] (2) Forming step: forming a film by solvent evaporation method or hot pressing method, wherein the thickness of the film is 50-300 μm;

[0013] (3) Post-treatment step: heat treating the film at a temperature of 100-150° C. for 1-3 hours, and then cooling to room temperature.

[0014] Preferably, the lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluorophosphate (LiPF6), or lithium thiocyanate (LiSCN).

[0015] Preferably, the polymer matrix is ​​at least one of polyethylene glycol dimethyl ether (PEGDME), polyethylene oxide (PEO), polyvinylidene fluoride (PVDF) or copolymers thereof, and the molecular weight of the polymer matrix is ​​in the range of 100,000-1,000,000.

[0016] Preferably, the inorganic filler is at least one of aluminum oxide (Al2O3), silicon dioxide (SiO2), lithium sulfide (Li2S) or boron nitride (BN), and the particle size of the inorganic filler is in the range of 10-500 nm.

[0017] Preferably, the ion conductive additive is at least one of lithium borate (LiBOB) and lithium phosphate (LiPO4).

[0018] Preferably, the conductive additive consists of the following components:

[0019] Zirconium aminophthalate MOF (CAS: 1260119-00-3): 175-350 parts;

[0020] 2-Methacrylate zinc salt (CAS: 13189-00-9): 20-40 parts;

[0021] 1,4-Dimethyl-2-pyrrolidone (CAS: 2555-04-6): 1000-1400 parts;

[0022] Triethylamine (CAS: 121-44-8): 2-5 parts;

[0023] (E)-3-(Thien-3-yl)ethyl acrylate (CAS: 50266-60-9): 0.04-0.5 parts.

[0024] Preferably, the method for preparing the conductive additive comprises the following steps:

[0025] According to the mass fractions, aminophthalate zirconium MOF and 2-methylacrylate zinc salt are added to 1,4-dimethyl-2-pyrrolidone, and triethylamine is added after stirring and mixing evenly, and then stirred and reacted at room temperature for 20-40 minutes; then (E)-3-(thiophene-3-yl) ethyl acrylate is added, the temperature is controlled at 60-80°C, the reaction is stirred for 100-120 minutes, and DMF is removed by reduced pressure distillation to obtain the conductive additive.

[0026] Preferably, the organic solvent is at least one of acetone, methanol and acetonitrile.

[0027] Preferably, the solvent volatilization method comprises drying at 85-120° C. for 4-8 hours; and the hot pressing method comprises a pressure of 10-15 MPa, a temperature of 100-120° C., and a pressing time of 10-60 minutes.

[0028] Preferably, the heat treatment step is performed under an inert gas atmosphere to avoid oxidation or decomposition of the material, and the inert atmosphere is one of nitrogen, argon or helium.

[0029] The reaction mechanism and excellent effects of the above conductive additives:

[0030] 1) Reaction mechanism

[0031] The aminophthalate zirconium MOF and 2-methacrylic acid zinc salt undergo an amino-acrylic addition reaction, and the aminophthalate zirconium MOF and (E)-3-(thiophene-3-yl)ethyl acrylate undergo an amino-acrylic addition reaction to obtain a zirconium phthalate MOF containing thiophene / acrylic acid zinc salt / ; it is used as a conductive additive,

[0032] 2) Technical Effect

[0033] The prepared solid lithium metal electrolyte exhibits the following excellent technical effects: High ionic conductivity: Due to the reasonable ratio of lithium salt, inorganic filler and ionic conductive additive, the ionic conductivity of the electrolyte is greatly improved, meeting the needs of high-power lithium metal batteries.

[0034] Through the amino-acryl addition reaction, the aminophthalate zirconium MOF formed stable chemical bonds with 2-methylacrylate zinc salt and (E)-3-(thiophen-3-yl) ethyl acrylate. These bonds not only enhanced the mechanical strength of the material, but also improved its thermal stability and electrochemical performance.

[0035] The introduction of thienyl and zinc acrylate makes the spatial structure of the material more complex and ordered. This ordered structure facilitates the transport and diffusion of ions, thereby improving the ionic conductivity of the material. In addition, the complex spatial structure also helps to inhibit the growth of lithium dendrites and improve the safety performance of the battery.

[0036] As a conductive additive, the thiophene-based / acrylic acid zinc salt / zirconium phthalate MOF exhibits excellent technical effects in solid-state lithium metal electrolytes. First, it greatly improves the ionic conductivity of the electrolyte, meeting the needs of high-power lithium metal batteries. Secondly, it also has good thermal and electrochemical stability, and can maintain stable performance under high temperature and high pressure environments. Finally, it can also effectively inhibit the growth of lithium dendrites and improve the safety performance of the battery.

[0037] The solid lithium metal electrolyte prepared by the method of the present invention exhibits the following excellent technical effects:

[0038] 1. High ionic conductivity: Due to the reasonable ratio of lithium salt, inorganic filler and ionic conductive additive, the

[0039] The ionic conductivity of the electrolyte is greatly improved, meeting the needs of high-power lithium metal batteries.

[0040] 2. Interface stability: The combination of inorganic fillers and polymer matrix significantly improves the interface stability between electrolyte and lithium metal

[0041] The interface stability between the negative electrodes reduces the risk of lithium dendrite formation.

[0042] 3. Thermal stability: The solid electrolyte exhibits excellent thermal stability at higher temperatures, which is beneficial

[0043] Extend battery life. DETAILED DESCRIPTION

[0044] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0045] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0046] Example 1

[0047] A highly conductive solid lithium metal electrolyte membrane and a preparation method thereof, characterized in that the steps include:

[0048] (1) Material mixing: 5 g of lithium salt, 40 g of polymer matrix, 5 g of inorganic filler, 2 g of ion conductive additive and 0.1 g of conductive additive were uniformly mixed, and then the mixture was dissolved in 450 g of organic solvent;

[0049] (2) Forming step: forming a film by solvent evaporation method, wherein the thickness of the film is 50 μm;

[0050] (3) Post-treatment step: heat treating the film at 100° C. for 3 hours, and then cooling to room temperature.

[0051] The lithium salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0052] The polymer matrix is ​​polyethylene glycol dimethyl ether (PEGDME).

[0053] The inorganic filler is alumina (Al2O3).

[0054] The ion conductive additive is lithium borate (LiBOB).

[0055] The conductive additive is composed of the following components:

[0056] Zirconium aminophthalate MOF (CAS: 1260119-00-3): 175 g;

[0057] 2-Methacrylate zinc salt (CAS: 13189-00-9): 20 g;

[0058] 1,4-Dimethyl-2-pyrrolidone (CAS: 2555-04-6): 1000g;

[0059] Triethylamine (CAS: 121-44-8): 2 g;

[0060] (E)-ethyl 3-(thiophen-3-yl)acrylate (CAS: 50266-60-9): 0.04 g.

[0061] The preparation method of the conductive additive comprises the following steps:

[0062] Zirconium aminophthalate MOF and zinc 2-methylacrylate are added to 1,4-dimethyl-2-pyrrolidone, and triethylamine is added after stirring and mixing evenly, and then stirred and reacted at room temperature for 20 minutes; then (E)-3-(thiophene-3-yl) ethyl acrylate is added, the temperature is controlled at 60°C, the reaction is stirred for 120 minutes, and DMF is removed by reduced pressure distillation to obtain the conductive additive.

[0063] The organic solvent is acetone.

[0064] The solvent evaporation method: drying at 85° C. for 8 h.

[0065] The heat treatment step is performed under an inert gas atmosphere to avoid oxidation or decomposition of the material, and the inert gas atmosphere is nitrogen.

[0066] Example 2

[0067] A highly conductive solid lithium metal electrolyte membrane and a preparation method thereof, characterized in that the steps include:

[0068] (1) Material mixing: 10 g of lithium salt, 50 g of polymer matrix, 15 g of inorganic filler, 4 g of ion conductive additive and 0.6 g of conductive additive were uniformly mixed, and then the mixture was dissolved in 600 g of organic solvent;

[0069] (2) Forming step: forming a film by solvent evaporation method, wherein the thickness of the film is 150 μm;

[0070] (3) Post-treatment step: heat treating the film at 125° C. for 2 hours, and then cooling to room temperature.

[0071] The lithium salt is lithium hexafluorophosphate (LiPF6).

[0072] The polymer matrix is ​​polyethylene oxide (PEO).

[0073] The inorganic filler is silicon dioxide (SiO2).

[0074] The ion conductive additive is lithium phosphate (LiPO4).

[0075] The conductive additive is composed of the following components:

[0076] Zirconium aminophthalate MOF (CAS: 1260119-00-3): 225 g;

[0077] 2-Methacrylate zinc salt (CAS: 13189-00-9): 30 g;

[0078] 1,4-Dimethyl-2-pyrrolidone (CAS: 2555-04-6): 1150g;

[0079] Triethylamine (CAS: 121-44-8): 3 g;

[0080] (E)-ethyl 3-(thiophen-3-yl)acrylate (CAS: 50266-60-9): 0.2 g.

[0081] The preparation method of the conductive additive comprises the following steps:

[0082] Zirconium aminophthalate MOF and zinc 2-methylacrylate are added to 1,4-dimethyl-2-pyrrolidone, and triethylamine is added after stirring and mixing evenly, and then stirred and reacted at room temperature for 30 minutes; then (E)-3-(thiophene-3-yl) ethyl acrylate is added, the temperature is controlled at 70°C, the reaction is stirred for 110 minutes, and DMF is removed by reduced pressure distillation to obtain the conductive additive.

[0083] The organic solvent is methanol.

[0084] The solvent evaporation method: drying at 100° C. for 6 hours.

[0085] The heat treatment step is performed under an inert gas atmosphere to avoid oxidation or decomposition of the material, and the inert gas atmosphere is nitrogen.

[0086] Example 3

[0087] A highly conductive solid lithium metal electrolyte membrane and a preparation method thereof, characterized in that the steps include:

[0088] (1) Material mixing: 15 g of lithium salt, 60 g of polymer matrix, 20 g of inorganic filler, 6 g of ion conductive additive and 1.5 g of conductive additive were mixed evenly, and then the mixture was dissolved in 750 g of organic solvent;

[0089] (2) Forming step: forming a film by solvent evaporation method, wherein the thickness of the film is 250 μm;

[0090] (3) Post-treatment step: The film is heat treated at a temperature of 140° C. for 2 hours, and then cooled to room temperature.

[0091] The lithium salt is lithium hexafluorophosphate (LiPF6).

[0092] The polymer matrix is ​​polyvinylidene fluoride (PVDF).

[0093] The inorganic filler is lithium sulfide (Li2S).

[0094] The ion conductive additive is lithium phosphate (LiPO4).

[0095] The conductive additive is composed of the following components:

[0096] Zirconium aminophthalate MOF (CAS: 1260119-00-3): 300 g;

[0097] 2-Methacrylate zinc salt (CAS: 13189-00-9): 30 g;

[0098] 1,4-Dimethyl-2-pyrrolidone (CAS: 2555-04-6): 1300g;

[0099] Triethylamine (CAS: 121-44-8): 4 g;

[0100] (E)-ethyl 3-(thiophen-3-yl)acrylate (CAS: 50266-60-9): 0.4 g.

[0101] The preparation method of the conductive additive comprises the following steps:

[0102] Zirconium aminophthalate MOF and zinc 2-methylacrylate are added to 1,4-dimethyl-2-pyrrolidone, and triethylamine is added after stirring and mixing evenly, and then stirred and reacted at room temperature for 30 minutes; then (E)-3-(thiophene-3-yl) ethyl acrylate is added, the temperature is controlled at 70°C, the reaction is stirred for 110 minutes, and DMF is removed by reduced pressure distillation to obtain the conductive additive.

[0103] The organic solvent is acetonitrile.

[0104] The solvent evaporation method: drying at 110° C. for 6 hours.

[0105] The heat treatment step is performed under an inert gas atmosphere to avoid oxidation or decomposition of the material, and the inert gas atmosphere is argon.

[0106] Example 4

[0107] A highly conductive solid lithium metal electrolyte membrane and a preparation method thereof, characterized in that the steps include:

[0108] (1) Material mixing: 20 g of lithium salt, 70 g of polymer matrix, 30 g of inorganic filler, 8 g of ion conductive additive and 2 g of conductive additive were mixed uniformly, and then the mixture was dissolved in 900 g of organic solvent;

[0109] (2) Forming step: forming a film by solvent evaporation method, wherein the thickness of the film is 300 μm;

[0110] (3) Post-treatment step: heat-treating the film at a temperature of 150° C. for 1 hour, and then cooling to room temperature.

[0111] The lithium salt is lithium thiocyanate (LiSCN).

[0112] The polymer matrix is ​​polyvinylidene fluoride (PVDF).

[0113] The inorganic filler is boron nitride (BN).

[0114] The ion conductive additive is lithium borate (LiBOB).

[0115] The conductive additive is composed of the following components:

[0116] Zirconium aminophthalate MOF (CAS: 1260119-00-3): 350 g;

[0117] 2-Methacrylate zinc salt (CAS: 13189-00-9): 40 g;

[0118] 1,4-Dimethyl-2-pyrrolidone (CAS: 2555-04-6): 1400g;

[0119] Triethylamine (CAS: 121-44-8): 5 g;

[0120] (E)-3-(Thien-3-yl)ethyl acrylate (CAS: 50266-60-9): 0.5 g.

[0121] The preparation method of the conductive additive comprises the following steps:

[0122] Zirconium aminophthalate MOF and zinc 2-methylacrylate are added to 1,4-dimethyl-2-pyrrolidone, and triethylamine is added after stirring and mixing evenly, and then stirred and reacted at room temperature for 40 minutes; then (E)-3-(thiophene-3-yl) ethyl acrylate is added, the temperature is controlled at 80°C, the reaction is stirred for 100 minutes, and DMF is removed by reduced pressure distillation to obtain the conductive additive.

[0123] The organic solvent is acetonitrile.

[0124] The solvent evaporation method: drying at 120° C. for 4 h.

[0125] The heat treatment step is performed in an inert gas atmosphere to avoid oxidation or decomposition of the material, and the inert gas atmosphere is helium.

[0126] Comparative Example 1

[0127] The preparation of the solid lithium metal electrolyte is basically the same as that of Example 1, except that no conductive additive is added in step (1).

[0128] Comparative Example 2

[0129] The preparation of the solid lithium metal electrolyte is basically the same as that of Example 1, except that no 2-methylacrylate zinc salt is added during the preparation of the conductive additive in step (1).

[0130] Comparative Example 3

[0131] The preparation of the solid lithium metal electrolyte is basically the same as that of Example 1, except that no (E)-3-(thiophene-3-yl) ethyl acrylate is added during the preparation of the conductive additive in step (1).

[0132] The test method of the solid lithium metal electrolyte film prepared in the above embodiment is as follows:

[0133] 1) Ionic conductivity test: The impedance of the sample was tested in the frequency range of 1Hz to 1MHz using the electrochemical workstation (EIS). The test temperature was room temperature and the test sample was a film with a diameter of 10 mm. The conductivity calculation formula is:

[0134] σ=L / (R*A)

[0135] Where σ is the conductivity, L is the film thickness, R is the impedance, and A is the electrode area.

[0136] 2) Thermal stability test: The thermal stability of the electrolyte was measured by a thermogravimetric analyzer (TGA) under a nitrogen atmosphere by heating from room temperature to 300°C at a heating rate of 10°C / min.

[0137] 3) Interface impedance test: The interface impedance between electrolyte and lithium metal is measured by electrochemical impedance spectroscopy (EIS). The test frequency range is 1 Hz to 1 MHz, the electrode material is lithium metal, and the measurement temperature is room temperature.

[0138] Table 1 Test results

[0139]

[0140] The above-mentioned embodiments significantly improve the ionic conductivity, interface stability and good thermal stability of the solid lithium metal electrolyte by introducing inorganic fillers and ion conductive additives, demonstrating its application potential in lithium metal batteries.

[0141] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A highly conductive solid lithium metal electrolyte membrane and a method for preparing the same, characterized in that: The following steps are involved: (1) Material mixing: 5-20 parts of lithium salt, 40-70 parts of polymer matrix, 5-30 parts of inorganic filler, 2-8 parts of ion conductive additive and 0.1-2 parts of conductive additive are uniformly mixed by mass, and then the mixture is dissolved in 450-900 parts of organic solvent; (2) Forming step: forming a film by solvent evaporation method or hot pressing method, wherein the thickness of the film is 50-300 μm; (3) Post-treatment step: heat treating the film at a temperature of 100-150° C. for 1-3 hours, and then cooling to room temperature.

2. A highly conductive solid lithium metal electrolyte membrane and a method for preparing the same according to claim 1, characterized in that: The lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluorophosphate (LiPF6), or lithium thiocyanate (LiSCN).

3. A highly conductive solid lithium metal electrolyte membrane and a method for preparing the same according to claim 1, characterized in that: The polymer matrix is ​​at least one of polyethylene glycol dimethyl ether (PEGDME), polyethylene oxide (PEO), polyvinylidene fluoride (PVDF) or copolymers thereof, and the molecular weight of the polymer matrix ranges from 100,000 to 1,000,000.

4. A highly conductive solid lithium metal electrolyte membrane and a method for preparing the same according to claim 1, characterized in that: The inorganic filler is at least one of aluminum oxide (Al2O3), silicon dioxide (SiO2), lithium sulfide (Li2S) or boron nitride (BN), and the particle size of the inorganic filler ranges from 10 to 500 nm.

5. A highly conductive solid lithium metal electrolyte membrane and a method for preparing the same according to claim 1, characterized in that: The ion conductive additive is at least one of lithium borate (LiBOB) and lithium phosphate (LiPO4).

6. A highly conductive solid lithium metal electrolyte membrane and a method for preparing the same according to claim 1, characterized in that: The conductive additive is composed of the following components: Zirconium aminophthalate MOF: 175-350 parts; 2-Methacrylate zinc salt: 20-40 parts; 1,4-dimethyl-2-pyrrolidone: 1000-1400 parts; Triethylamine: 2-5 parts; (E)-3-(Thien-3-yl)ethyl acrylate: 0.04-0.5 parts.

7. A highly conductive solid lithium metal electrolyte membrane and a method for preparing the same according to claim 6, characterized in that: The preparation method of the conductive additive comprises the following steps: According to the mass fractions, aminophthalate zirconium MOF and 2-methylacrylate zinc salt are added to 1,4-dimethyl-2-pyrrolidone, and triethylamine is added after stirring and mixing evenly, and then stirred and reacted at room temperature for 20-40 minutes; then (E)-3-(thiophene-3-yl) ethyl acrylate is added, the temperature is controlled at 60-80°C, the reaction is stirred for 100-120 minutes, and DMF is removed by reduced pressure distillation to obtain the conductive additive.

8. A highly conductive solid lithium metal electrolyte membrane and a method for preparing the same according to claim 1, characterized in that: The organic solvent is at least one of acetone, methanol and acetonitrile.

9. A highly conductive solid lithium metal electrolyte membrane and a method for preparing the same according to claim 1, characterized in that: The solvent volatilization method: drying at 85-120° C. for 4-8 hours; the hot pressing method: pressure of 10-15 MPa, temperature of 100-120° C., pressing time of 10-60 minutes.

10. A highly conductive solid lithium metal electrolyte membrane and a method for preparing the same according to claim 1, characterized in that: The heat treatment step is performed under an inert gas atmosphere to avoid oxidation or decomposition of the material. The inert gas atmosphere is one of nitrogen, argon or helium.

Citation Information

Cited By

  • Solid electrolyte of solid lithium battery

    CN119994156A